PENGARUH LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA KELURAHAN ATAKKAE KECAMATAN TEMPE, KABUPATEN WAJO - Muhammad Justiawal (Universitas Mbojo Bima, 2023)
The work environment can affect employee emotions. If employees like the work environment in which they work, then these employees will feel comfortable at work to carry out activities because work time is used properly and optimistically so that employee performance will also be better. The work environment includes working relationships that are formed between fellow employees, both working relationships between subordinates and superiors as well as the physical or non-physical environment. The purpose of this study was to determine whether there is an influence of the work environment on employee morale at the Atakkae Village Office, Tempe District, Wajo Regency and to measure how big the influence is. This type of research is classified as a survey with a descriptive quantitative approach, where the data obtained from 12 respondents who are samples are then processed using statistics and presented in the form of scientific analysis. After collecting data through observation, documentation and questionnaires in the field, it is then analyzed using the person product moment correlation test. The results of this study indicate that implementation, work environment have a positive and significant effect on employee morale. The results of the study show that the results of each dimension reach an average of the Good category.